A new approach to treating sleep disorders? - Medical marijuana review - Gondko, Daniel; Dębiec, Patrycja; Roman, Jakub; Pietrzak, Nikodem (Journal of Education, Health and Sport, 2024)
Insomnia, defined as difficulty falling or staying asleep, significantly impacts the quality of life and mental health of people worldwide. In recent years, there has been growing interest in using medical marijuana as an alternative treatment method for various conditions, including sleep disorders. The purpose of this review is to examine the available scientific evidence regarding the efficacy and safety of using medical marijuana in the treatment of insomnia. Analyzing data from clinical, observational, and experimental studies, this work aims to present a comprehensive picture of the potential benefits and risks associated with such treatment. This review seeks to provide doctors, patients, and policymakers with up-to-date information that can support the decision-making process regarding the use of medical marijuana as an adjunct therapy in the treatment of insomnia, highlighting both the therapeutic potential and the need for further research in this field.